ChemInform Abstract: Multicomponent Domino Reactions of Hydrazinecarbodithioates: Concise Access to 3‐Substituted 5‐Thiol‐1, 3, 4‐thiadiazolines. Issue 49 (December 2015) - Jia, Huihui; Feng, Huangdi; Sun, Zhihua
Abstract: An addition‐cycloaddition cascade of hydrazinecarbodithioates with formaldehyde and propynoic acids under mild conditions affords thiadiazole‐based thioethers.